PERUBAHAN KARAKTERISTIK BUBUK BUAH PANDAN (Pandanus tectorius) SELAMA PENYIMPANAN PADA PERLAKUAN JENIS KEMASAN DAN SUHU PENYIMPANAN - Budha Astawa, I Komang; Wartini, Ni Made; Sedana Yoga, I Wyn Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): Juni, 2019)
Pandan is part of the marine pandanus plants that are yellow to orange. Pandan fruit has the potential to be a source of natural dyes yellow and orange. Dyes obtained from pandan fruit are unstable. The purpose of this study was to determine the effect of the type of packaging and storage temperature on the characteristics of fruit powder and to determine the type of packaging and the best temperature for storing pandan powder. The design in this study used a completely randomized design with two factors. Factor I is a packaging treatment consisting of 4 types of packaging, namely polypropylene, polyethylene, aluminum foil, and brown paper. Factor II is the temperature consisting of two levels, namely 4º±2ºC and 27º±2ºC. The results showed that the temperature had a very significant effect (P<0,01) on water content and total carotene but did not have a significant effect (P>0,05) on the reddish value (L*), the reddish value (a*), reddish value (b*). The packaging type has a very significant effect (P<0.01) on water content and total carotene, but does not have a significant effect (P>0,05) on the reddish value (L*), the reddish value (a*), reddish value (b*), the most stable treatment in aluminum foil and cold temperatures 4 ± 2ºC for 4 weeks of storage, with the percentage of moisture content, total carotenoids, color intensity (L *, a *, b *) in the amount of 14.00%, 17.86%, 34,89%, 43,88%, 22,76% Keywords : pandanus (Pandanus tectorius), carotene, type of packaging, storage temperature.